A Defective Crosstalk Between Neurons and Müller Glial Cells in the rd1 Retina Impairs the Regenerative Potential of Glial Stem Cells - Volonté, Yanel A.; Vallese-Maurizi, Harmonie; Dibo, Marcos J.; Ayala-Peña, Victoria B.; Garelli, Andrés; Zanetti, Samanta R.; Turpaud, Axel; Craft, Cheryl Mae; Rotstein, Nora P.; Politi, Luis E.; German, Olga L. (Frontiers in Cellular Neuroscience, 2019)
Abstract Müller glial cells (MGC) are stem cells in the retina. Although their regenerative capacity is very low in mammals, the use of MGC as stem cells to regenerate photoreceptors (PHRs) during retina degenerations, such as in retinitis pigmentosa, is being intensely studied. Changes affecting PHRs in diseased retinas have been thoroughly investigated; however, whether MGC are also affected is still unclear. We here investigated whether MGC in retinal degeneration 1 (rd1) mouse, an animal model of retinitis pigmentosa, have impaired stem cell properties or structure. rd1 MGC showed an altered morphology, both in culture and in the whole retina. Using mixed neuron-glial cultures obtained from newborn mice retinas, we determined that proliferation was significantly lower in rd1 than in wild type (wt) MGC. Levels of stem cell markers, such as Nestin and Sox2, were also markedly reduced in rd1 MGC compared to wt MGC in neuron-glial cultures and in retina cryosections, even before the onset of PHR degeneration. We then investigated whether neuron-glial crosstalk was involved in these changes. Noteworthy, Nestin expression was restored in rd1 MGC in co-culture with wt neurons. Conversely, Nestin expression decreased in wt MGC in co-culture with rd1 neurons, as occurred in rd1 MGC in rd1 neuron-glial mixed cultures. These results imply that MGC proliferation and stem cell markers are reduced in rd1 retinas and might be restored by their interaction with “healthy” PHRs, suggesting that alterations in rd1 PHRs lead to a disruption in neuron-glial crosstalk affecting the regenerative potential of MGC.